Role of patient safety attitudes between career identity and turnover intentions of new nurses in China: A cross-sectional study - Zhang, Man; Zheng, Xutong; Chen, Changchang; Fang, Jiaxin; Liu, Huan; Zhang, Xiancui; Lang, Hongjuan (Frontiers in Public Health, 2022)
Background Patient safety is a key priority for healthcare systems, which is not only about the safety and quality development of health care but also about the safety of patients' lives. However, there has been little research exploring the relationship between new nurses' willingness to leave, patient safety culture, and professional identity. This study was to explore patient safety for new nurses, examine the relationship between professional identity, patient safety culture, and turnover intentions of newly recruited nurses in China, and validate the mediating role of patient safety culture. Methods From August 2019 to September 2021, we collected data from newly recruited nurses in 5 large tertiary public hospitals in Anhui Province, China using a questionnaire survey. Descriptive analysis, a univariate analysis, Pearson correlation analysis, and mediated regression analysis were used to estimate the current status of patient safety attitudes and the effect of safety culture on career identity and turnover intentions among newly recruited nurses. Results The turnover intention of 816 newly recruited nurses was 14.16 ± 3.14%. Patient safety culture was positively associated with career identity (r = 0.516, P < 0.01) and negatively associated with turnover intentions (r = −0.437, P < 0.01), while patient safety was also a partial mediator between career identity and turnover intentions. Conclusions The results showed that the low patient safety attitudes of new nurses in China should not be ignored. The impact of professional identity on patient safety has important practical implications for promoting a culture of safety among new nurses and reducing turnover rates.